(untitled) (Journal of Partial Differential Equations, 2001)
A complete convergence nnalysis is given for two-level scheme of the alternating-direction implicit characteristic finite element method for the approximate solution of the three-dimensional generalized nerve conduction equation. By use of the calculation of vector product, H^-1 norm estimates, and a priori estimate theory and technique, the optimal order estimate in L² is obtained.